AKTIVITAS ANTIOKSIDAN DAN PENERIMAAN PANELIS TEH BUBUK DAUN ALPUKAT (Persea Americana Mill.) BERDASARKAN LETAK DAUN PADA RANTING - Abdul Rauf; Usman Pato; Dewi Fortuna Ayu (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research was to find out the effect of leaf age toward the antioxidant activity and acceptance of avocado leaves herbal tea by panelists. This research used a Completely Randomized Design Experiment with four treatments and four repetitions. The treatment applied toward the avocado leaves herbal tea were P1 : shoots (the first leaves appeared on the top of the branches), P2 : young leaves (the 1st–3rd leaves after the shoot), P3: medium old leaves (the 4th–6th leaves after the shoot), and P4 : old leaves (the 7th–9th leaves after the shoot). Collected data were statistically analized using ANOVA and DNMRT at 5% level. The results showed that the leaves age significantly affected on water content, ash, polyphenol, antioxidant activity and sensory assesment descriptive and hedonic. The choosen treatment from the results of this research was P1 (the first leaves appeared on the top of the branches) that had 5,67% of moisture content, 3,27% of ash content, 7,33% polyphenol content, 54,69 µg/mL of antioxidant activity (IC50). The results of descriptive assesment showed that tea of avocado leaves had yellow brownish color, slightly unpleasent scent, and a little slightly bitter taste. Hedonic assesment showed avocado leaf tea had favored colors, quite fond sense, and the overall assessment of tea was quite favored. Keywords: Herbal tea, avocado, leaf position on the branch, antioxidant activity, panelists acceptance